Pengaruh profitabilitas, solvabilitas, likuiditas dan audit tenure terhadap audit report lag dengan komite sebagai pemoderasi - Ryan Rich Tampubolon; Valentine Siagian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This study aims to examine empirical evidence regarding the effect of profitability, solvency, liquidity, and audit period on the audit report with the audit committee as a moderating variable. This research was conducted by a quantitative method with a descriptive approach. The population in this study are property, real estate, and construction companies listed on the Indonesia Stock Exchange (BEI) in 2016-2019. The sampling method used was the purposive sampling method. The sample in this study was 184 firm year observations. Data analysis used multiple linear regression analysis and moderated regression analysis with interaction test. The results of this study indicate that profitability has a significant negative effect on audit report lag, solvency has a significant negative effect on audit report lag, liquidity has a significant positive effect on audit report lag, and audit tenure has a significant positive effect on audit report lag. The audit committee as a moderating variable strengthens all independent variables on the dependent variable. For further researchers, it is recommended to increase the sample size and expand the object of research by researching sectors that have more companies and also increasing the period of research.